2012
DOI: 10.1093/schbul/sbs064
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Transglutaminase 6 Antibodies in Sera From Schizophrenia Patients

Abstract: Gluten can cause extraintestinal manifestations with or without gastrointestinal symptoms and elevated antitissue transglutaminase 2 (tTG2) autoantibodies. Organ-specific gluten reaction involves immune response toward other transglutaminase (TG) isoforms including tTG3 (expressed in the skin, leading to dermatitis herpetiformis) and tTG6 (expressed in the brain, causing gluten ataxia). This analysis focuses on tTG6 antibodies, which have never been studied before in schizophrenia (SZ) and its relationships to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Patients seropositive for TG6 IgA antibodies showed a clinical presentation similar to that of patients negative for these antibodies regarding age at disease onset, proportion of bulbar cases, and sex distribution, much like the presentation of patients with schizophrenia. 15 This similarity opposes the reported relatively early onset of disease in patients with gluten ataxia who are seropositive for TG6 IgA antibodies. 24 Production of TG6 autoantibodies was not significantly associated with a familial history of ALS.…”
Section: Clinical Presentation In Patients With or Without Tg6 Autoanmentioning
confidence: 76%
See 1 more Smart Citation
“…Patients seropositive for TG6 IgA antibodies showed a clinical presentation similar to that of patients negative for these antibodies regarding age at disease onset, proportion of bulbar cases, and sex distribution, much like the presentation of patients with schizophrenia. 15 This similarity opposes the reported relatively early onset of disease in patients with gluten ataxia who are seropositive for TG6 IgA antibodies. 24 Production of TG6 autoantibodies was not significantly associated with a familial history of ALS.…”
Section: Clinical Presentation In Patients With or Without Tg6 Autoanmentioning
confidence: 76%
“…The TG6 antibody titer is dependent on gluten ingestion. 14 In addition, TG6 antibodies have been reported in gluten neuropathy, 12 schizophrenia, 15 cerebral palsy, 16 and a rare neurologic syndrome associated with epilepsy and cerebral calcification. 17 Other neurologic syndromes, such as epilepsy, encephalopathy, dementia, myopathy, myelopathy, multiple sclerosis, stiffman syndrome, and myoclonic ataxia, have been rarely reported in association with gluten sensitivity.…”
mentioning
confidence: 99%
“…The analysis was focused on tTG6 antibodies and their relationship to anti-tissue transglutaminase 2 (tTG2) and to antigliadin antibodies. Results indicated a higher prevalence of tTG6 antibodies in schizophrenia and confirmed that it may be a useful biomarker to identify patients whose gluten-free diet can potentially contribute to the improvement of symptoms (Cascella et al, 2012). …”
Section: Immunologic Studies (Reported By M Dmitrzak-węglarz Alekmentioning
confidence: 73%
“…An immune-mediated reaction to gluten could trigger a neuroinflammatory process, with associated impairment of the permeability of the blood-brain barrier. We recently reported an increased prevalence of antibodies for transglutaminase 6, specifically expressed in the brain, in schizophrenia patients who were positive for AGA antibodies (25). We described the findings as a marker of neuroinflammation in gluten-sensitive schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%